Pengaruh Beban Kerja, Kompensasi dan Kepuasan Kerja Terhadap Produktivitas Kerja Dosen dalam Publikasi Jurnal Ilmiah di Universitas Flores - Marlona Ihalauw; Hyronimus Se; Mansyur Abdul Hamid (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analyze the influence of workload, compensation and job satisfaction on lecturers' work productivity in scientific journal publications at Flores Ende University. Using a quantitative approach, data was collected through questionnaires from 71 respondents. Data analysis was carried out using multiple linear regression. The research results show that work responsibilities, compensation and job satisfaction simultaneously have a significant effect on lecturers' work productivity and the F value count equal to 32.173 > F table 2.640 with a significance of 0.000 < 0.05. The coefficient of determination shows that 57.2% of changes in teacher performance are explained by the three independent variables. The conclusion of this research is that an effective workload, fair compensation system and increased job satisfaction will increase lecturers' work productivity in scientific journal publications. These findings have important implications for the development of policies and strategies to increase lecturer work productivity in the research field.